2018
DOI: 10.1136/jmedgenet-2018-105288
|View full text |Cite
|
Sign up to set email alerts
|

PEHO syndrome: the endpoint of different genetic epilepsies

Abstract: BackgroundProgressive encephalopathy, hypsarrhythmia and optic atrophy (PEHO) has been described as a clinically distinct syndrome. It has been postulated that it is an autosomal recessive condition. However, the aetiology is poorly understood, and the genetic basis of the condition has not been fully elucidated. Our objective was to discover if PEHO syndrome is a single gene disorder.MethodChildren with PEHO and PEHO-like syndrome were recruited. Clinical, neurological and dysmorphic features were recorded; E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…A frequently detected missense variant, NM_021222.3:c.316G > A (p.(D106N)), which affects a conserved Aspartate in the DHH motif, was found in a large number of patients (about one‐third of the reported families). These patients presented with a wide spectrum of typical and atypical phenotypes, including developmental and epileptic encephalopathies, PEHO syndrome (progressive encephalopathy with peripheral edema, hypsarrhythmia, and optic atrophy), as well as a spinal muscular atrophy phenotype with signs of neurogenic muscular atrophy (Chitre et al., 2018; Iacomino et al., 2018; Okur et al., 2019; Papuc et al., 2019). It is likely that NM_021222.3:c.316G > A (p.(D106N)) lies in a mutational hotspot, given the different ethnic backgrounds of the reported patients.…”
Section: Discussionmentioning
confidence: 99%
“…A frequently detected missense variant, NM_021222.3:c.316G > A (p.(D106N)), which affects a conserved Aspartate in the DHH motif, was found in a large number of patients (about one‐third of the reported families). These patients presented with a wide spectrum of typical and atypical phenotypes, including developmental and epileptic encephalopathies, PEHO syndrome (progressive encephalopathy with peripheral edema, hypsarrhythmia, and optic atrophy), as well as a spinal muscular atrophy phenotype with signs of neurogenic muscular atrophy (Chitre et al., 2018; Iacomino et al., 2018; Okur et al., 2019; Papuc et al., 2019). It is likely that NM_021222.3:c.316G > A (p.(D106N)) lies in a mutational hotspot, given the different ethnic backgrounds of the reported patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chitre et al recently evaluated 19 children from 11 families; seven had PEHO and 12 had PEHO-like syndrome and a pathogenic genetic variant was identified in 15 of them (PCLO, SCN2A, PLAA, UBA5, CASK, CCDC88 and SCN1A gene (Chitre et al, 2018). Based on their results, the authors concluded that PEHO and PEHO-like syndrome are clinically and genetically diverse entities and represent the endpoint of many severe epileptic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In their research article, Innes, McInnes, and Dyment review the literature and provide evidence that both clinical and molecular/causal heterogeneity is likely the primary explanation why a major gene has yet to be identified for this disorder (Innes, McInnes, & Dyment, ). The same phenomenon is likely underlying the complexity of other recognizable conditions not included in this issue, including Toriello‐Carey syndrome (Toriello, Colley, & Bamshad, ), Fryns syndrome (Bone et al, ; Thompson & Cole, ), PEHO syndrome (Chitre et al, ), and 3C syndrome (Elliott et al, ; Kolanczyk et al, ). Ideally, an underlying and possibly novel gene will be identified for some of the patients that were initially reported with Dubowitz syndrome (or most closely resemble such patients) to provide clarity on the spectrum of clinical features of this and similar syndromes and ultimately identify common biological pathways that might explain the phenotypic overlap among the reported patients.…”
Section: Themes Of the Issuementioning
confidence: 91%